Preparation of Natural Food-Grade Core-Shell Starch/Zein Microparticles by Antisolvent Exchange and Transglutaminase Crosslinking for Reduced Digestion of Starch - Wang, Chaofan; Qin, Kaili; Sun, Qingjie; Qiao, Xuguang (Frontiers in Nutrition, 2022)
The purpose of this study was to slow down the digestibility of starch granules by encapsulating it in zein shells. Drop of swollen corn starch granule suspension into thermal-treated zein ethanolic solution enables antisolvent precipitation of thermal-treated zein on the surface of swollen corn starch granules, leading to the formation of core-shell starch/zein microparticles. Confocal laser scanning microscopy images showed that swollen corn starch granules were coated by thermal-treated zein shells with a thickness of 0.48–0.95 μm. The volume average particle diameter of core-shell starch/zein microparticles was 14.70 μm and reached 18.59–30.98 μm after crosslinking by transglutaminase. The results of X-ray diffraction and Fourier transform infrared spectroscopy demonstrated that an interaction occurred between the swollen corn starch granules and the thermal-treated zein. The results for thermodynamic characteristics, pasting properties, and swelling power indicated that the compact network structure of core-shell starch/zein microparticles crosslinked by transglutaminase could improve starch granule thermal stability and resistance to shearing forces. Compared to native corn starch, the peak gelatinization temperatures of core-shell starch/zein microparticles increased significantly (p < 0.05), with a maximum value of 76.64 ℃. The breakdown values and the swelling power at 95 ℃ of core-shell starch/zein microparticles significantly (p < 0.05) decreased by 52.83–85.66% and 0.11–0.28%, respectively. The in vitro digestibility test showed that the contents of slowly digestible starch and resistant starch in the core-shell starch/zein microparticles increased to ~42.66% and ~34.75%, respectively, compared to those of native corn starch (9.56% and 2.48%, respectively). Our research supports the application of food-grade core-shell starch/zein microparticles to formulate low-digestibility food products.